PENGEMBANGAN WISATA KULINER TRADISIONAL PASAR KAMU SEBAGAI ALTERNATIF PENINGKATAN PEREKONOMIAN MASYARAKAT DESA - Falahi, Adrial; Tukimin (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2023)
The development of traditional culinary tourism has an important role in improving the economy of rural communities. This study aims to analyze the potential and strategy for developing culinary tourism in Pasar Kamu as an alternative to improving the economic welfare of local communities. The research method used is a qualitative approach with observation, interview, and literature study techniques. The results of the study indicate that Pasar Kamu has a strong tourist attraction through the uniqueness of traditional cuisine, cultural values, and support from the local community. However, there are several challenges such as lack of promotion, inadequate infrastructure, and limited product innovation. Therefore, development strategies that can be applied include improving the quality of culinary products, optimizing digital marketing, and collaborating with the government and tourism industry players. With the right strategy, Pasar Kamu has the potential to become a leading culinary tourism destination that contributes to improving the economy of rural communities in a sustainable manner.